Inequality Measures, Equivalence Scales and Adjustment for Household Size and Composition - Paolo Figini (Luxembourg Income Study (LIS), 1998)
Total household income inequality can be very different from inequality measured at the income per-capita level but only in recent years has the patter of this divergence been investigated. In this paper, result form Coulter et al. (1992) using a one-parameter equivalence scale are updated using data for Ireland, Italy, the UK and the US. A class of two-parameter equivalence scales, representing relative weights of adults and children, is then analyzed. Results are shown to depend on the correlation between household size, household composition and household income. Inequality generally increases with children's weight and decreases with adults' weight. OECD and other two-parameter equivalence scales empirically used show a similarity of results to one-parameter equivalence scales with elasticity around 0.5.
Keywords: 330; Einkommensverteilung; Messung; Theorie; Irland; USA; Großbritannien; Italien